Proven Inhibitory Effect on Lipopolysaccharides- Induced Nitric Oxide Production of Zanthoxylum rhetsa under Accelerated Condition and Stability Affecting Factors - Imphat, Chureeporn; Thongdeeying, Pakakrong; Itharat, Arunporn; Panthong, Sumalee; Makchuchit, Sunita (Asian Medical Journal and Alternative Medicine, 2021)
Introduction: Zanthoxylum rhetsa preparations were used in ethnomedicine for the treatments of muscle and tendon spasms. The essential oil from its fruit has been reported for its anti-inflammatory activity and previous study has shown that the hexane extract of Z.rhetsa pericarp showed highest in vitro anti-inflammatory effect. Nitric oxide (NO) is an inflammatory mediator associated with osteoarthritis. Therefore, in vitro production inhibition of NO in RAW264.7 macrophages was performed. The accelerated stability test and the forced degradation test were studied to estimate storage life and to ensure appropriate conditions for its activity. Methods: The hexane extracts obtained from the pericarp (PHE), fruit (FHE) and seed (SHE) were tested for production inhibition of LPS-induced NO in RAW264.7 macrophages. The active extract was treated with accelerated storage conditions and stress conditions and assessed for the LPS-induced NO production inhibition. Results: PHE showed the most potent activities on NO (IC50 11.99 ± 1.66 μg/ml) production inhibition but less active than prednisolone. After accelerated stability test, the activity of PHE was less stable than 30 days. Forced degradation on PHE revealed that oxidation condition did not affect NO production inhibition while moisture, heat and alkaline conditions weakened its activity. The acidic condition rendered PHE to be inactive. Conclusion: PHE was the most active fraction for NO production inhibition associated with osteoarthritis. Its estimated shelf-life was between 9 to 12 months at room temperature. However, moisture, heat, alkaline, and acid conditions should be avoided in order to maintain its activity.